Changing patterns of clinical decision making: are falling numbers of antibody incompatible transplants related to the increasing success of the UK Living Kidney Sharing Scheme? A national cohort study. (20th November 2020) - Manook, Miriam; Johnson, Rachel; Robb, Matthew; Burnapp, Lisa; Fuggle, Susan V.; Mamode, Nizam
Summary: Antibody incompatibility is a barrier to living kidney transplantation; antibody incompatible transplantation (AIT) is an accepted treatment modality, albeit higher risk. This study aims to determine changes to clinical decision making and access to AIT in the UK. An electronic survey was sent to all UK renal transplant centres ( n = 24), in 2014, and again in 2018. Questions focused on entry & duration in the UKLKSS for HLA and ABO‐incompatible pairs, Can and provision of direct AIT transplantation within those centres. Between 2014 & 2018, the duration recommended for patients in the UKLKSS increased. In 2014, 34.8% of centres reported leaving HLA‐i pairs in the UKLKSS indefinitely, or reviewing on a case by case basis, by 2018 this increased to 61%. Centres offering direct HLA‐i transplantation reduced from 58% to 37%. For low titre (1:8) ABO‐i recipients, 66% of centres recommended at least 9 months (3 matching runs) in the UKLKSS scheme in 2018, compared to 47% in 2014, 50% fewer units consider direct ABO‐i transplantation for unsuccessful pairs with high ABO titres (>1:512). Over time, clinicians appear to be facilitating more conservative management of AIT patients, potentially limiting access to living donor transplantation.